The Dark Side of Ridesharing in China: A Case Study of Qiangsheng Taxi - Tian Meng; Songyi Cai; You Qu; Evelyn Ng; Barney Tan; Bo Zhu (Discrete Dynamics in Nature and Society)
Our understanding of the negative implications of the sharing economy is limited, particularly from the perspective of the traditional businesses that are being displaced. To address this knowledge gap, this paper documents our ongoing study of Qiangsheng Taxi, the oldest and largest taxi company based in Shanghai, China. Our aim is to develop a preliminary process model based on the data collected to date that sheds light on the negative implications of ridesharing, one of the most recognized forms of the sharing economy. More specifically, our process model suggests that there are contextual conditions that are particularly conducive to the growth of ridesharing platforms in China and how they accumulate resources, which give rise to four negative outcomes for the traditional taxi business. These negative outcomes, in turn, reinforce the prevailing contextual conditions to form a vicious cycle that exacerbates the negative influence of the ridesharing platforms even further.